ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN TATA RIAS PENGANTIN PUTRI JENGGOLO PADA MASYARAKAT SIDOARJO - Iklil Shinta Prameswari; Nia Kusstianti; Octaverina Kecvara Pritasari; Maspiyah (Program Studi Pendidikan Tata Rias, 2026)
Putri Jenggolo bridal makeup is a traditional bridal makeup style originating from Sidoarjo. Based on interviews with several makeup artists in Sidoarjo, it was found that public interest in Putri Jenggolo bridal makeup is relatively low compared to traditional bridal makeup styles from other regions. This study aims to analyze the factors that influence the selection of Putri Jenggolo bridal makeup among the people of Sidoarjo. The research method used is a mixed method, combining a quantitative approach through questionnaires distributed to 30 brides or prospective brides, and a qualitative approach through interviews with 4 makeup artists from four beauty studios across three sub-districts in Sidoarjo Regency. The variables examined include cultural factors, social factors, and personal factors. Based on the data analysis, the findings show that cultural factors contribute 14% to the selection of bridal makeup, social factors contribute 13%, while personal factors contribute 14%. Most respondents fall into the moderate category in all three factors, indicating potential to increase interest through more intensive education and socialization. The study also found that personal factors have the most dominant influence in the selection of Putri Jenggolo bridal makeup, followed by cultural factors, and lastly social factors. The lack of public knowledge about Putri Jenggolo bridal makeup is identified as the main obstacle. These findings recommend more effective cultural promotion strategies to enhance public recognition and interest in Putri Jenggolo bridal makeup. Keywords: Factor Analysis, Putri Jenggolo Bridal Makeup